Modeling, Simulation, and Optimization 4.0 for a Distillation Column. Issue 7 (29th April 2020) - Asprion, Norbert
Abstract: Simulation is besides experimentation a key technology in design, analysis and operation of distillation columns. The reliability of simulations to answer questions concerning the real process strongly depends on model quality, which needs to be reliable and predictive. Usually available plant data can be used to validate and if necessary, to improve the model. In this contribution challenges and opportunities of a continuous model improvement in a flowsheet simulator with emphasis on new possibilities triggered by digitalization will be discussed. Abstract : The reliability of simulation and optimization results depends on the agreement of the model with reality. In this work a framework to support the setup of process models for various what‐if‐scenarios is presented. Challenges and opportunities triggered by digitalization are discussed.